2013
DOI: 10.1371/journal.pone.0075349
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and Expression of Calpain Family Members in Relation to Nutritional Status, Diet Composition and Flesh Texture in Gilthead Sea Bream (Sparus aurata)

Abstract: Calpains are non-lysosomal calcium-activated neutral proteases involved in a wide range of cellular processes including muscle proteolysis linked to post-mortem flesh softening. The aims of this study were (a) to characterise several members of the calpain system in gilthead sea bream and (b) to examine their expression in relation to nutritional status and muscle tenderisation. We identified the complete open reading frame of gilthead sea bream calpains1-3, sacapn1, sacapn2, sacapn3, and two paralogs of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 59 publications
(77 reference statements)
3
47
1
Order By: Relevance
“…Several members of the main proteolytic systems have been characterized and their responses upon different experimental challenges investigated in different fish species 18,[55][56][57][58][59][60] , including gilthead sea bream [20][21][22] ; however, due to the different experimental conditions (i.e. duration of periods, fish age, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several members of the main proteolytic systems have been characterized and their responses upon different experimental challenges investigated in different fish species 18,[55][56][57][58][59][60] , including gilthead sea bream [20][21][22] ; however, due to the different experimental conditions (i.e. duration of periods, fish age, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…This is more important in fish that have a specific and enhanced protein metabolism. The main endogenous proteolytic systems, each one performing specific degradative or regulatory functions according to the nutritional conditions are, calpains, cathepsins and ubiquitin-proteasome, all of which are well-known in fish, especially salmonids [17][18][19] , but also in gilthead sea bream [20][21][22] .In addition to muscle, bone is also an important tissue for skeletal and locomotion functions, but also, as a reservoir of minerals that is clearly affected when nutrition is restricted. Essential during development, synchronicity between bone and muscle is required for proper musculoskeletal growth 23,24 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited knowledge on the hormonal control of lipid turnover in fish adipose tissue [7][8][9]. It has been reported that growth hormone (GH), in addition to being a growth promoter, exerts a lipolytic effect in gilthead sea bream adipocytes [7,10]. GH transgenic coho salmon [11] are shown to increase their utilization of lipids for synthetic roles to maintain accelerated growth, but the specific effects in adipose tissue of GH overexpression remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin also stimulates lipoprotein lipase (LPL) activity in rainbow trout adipose tissue [17] and reduces the basal lipolysis level in rainbow trout and gilthead sea bream adipocytes [7,8]. Insulin-like growth factor (IGF)-I is structurally and functionally similar to insulin but is more potent as a growth factor and a metabolic controller in rainbow trout and gilthead sea bream myocytes and adipocytes [10,14,15,18]. In vertebrates, many of the growth-promoting actions of GH are known to be mediated indirectly through the stimulation of IGF transcription, mainly by the liver, or locally by extra hepatic tissues [19], but the mechanisms of action involved in GH proliferative and metabolic effects in fish are not well known [20].…”
Section: Introductionmentioning
confidence: 99%